2018
DOI: 10.1186/s40703-018-0096-9
|View full text |Cite
|
Sign up to set email alerts
|

Premature failure of a major highway in southwestern Nigeria: the case of Ipele–Isua highway

Abstract: Economic importance of road has increased enormously over the last decades in Nigeria and to a large extent, they are complementary to other modes of transportation. However, the deterioration of a road begins soon after construction. Some of the roads in Nigeria do not last up to 5 years before failure becomes imminent. Road failure has been defined in different ways by various authors. According to [14], a road stretch is said to have failed when a part or all the parts of the road surface or any part of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Hence, they are not suitable as subgrade, subbase and base materials. High variation in the moisture content causes large volume changes in the clayey soils [49]. The moisture content ranges from favorable, marginal favorable to unfavorable road construction materials in relation to the work of [55].…”
Section: Index Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, they are not suitable as subgrade, subbase and base materials. High variation in the moisture content causes large volume changes in the clayey soils [49]. The moisture content ranges from favorable, marginal favorable to unfavorable road construction materials in relation to the work of [55].…”
Section: Index Propertiesmentioning
confidence: 99%
“…Geotechnical investigation of subsoils helps in the understanding of soil's behavior that can cause significant damage to road construction and also proffers solutions in solving problems associated with both expansive or unexpansive soils [11, 14-17, 22, 23, 27, 28, 30-43]. Studies have also reiterated the contribution of solely geophysical studies and integration of geophysical and geotechnical studies in the investigation of causative factors for incessant failures of highways in parts of southwestern Nigeria [5,33,[44][45][46][47][48][49]. In order to avoid the reoccurrence of premature road failure of Isinbode-Ara road, geotechnical parameters of the residual subsoils which include the natural moisture content, grain size analysis, Atterberg limits, California bearing ratio, consolidation and permeability tests have been investigated to determine their behavior when subjected to loads.…”
Section: Introductionmentioning
confidence: 99%
“…However, the appropriateness of soils as base course or subbase course and the subgrade are in cogent connection to the conveyance and bearing of axle load which determine the strength, durability and life of roads [22,23]. Geotechnical assessment of subsoils helps in comprehending the behaviour of the soils that can cause remarkable impairment to road construction and also propose solutions in problems connected with both expansive and unexpansive soils [24][25][26]. Past investigations have also emphasized the role of geophysical investigations and integrated geotechnical and geophysical investigations in the investigation of the significant factors responsible for ceaseless highway pavement failures in parts of southern Nigeria [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Transport minimizes the time for the movement of people and goods, thus transport gives utility to economic activities and facilitates quick economic development. Road transportation is an important element in the physical development of any society as it controls the direction and extent of development (Daramola et al 2018). The attention of the researcher was drawn to a road failure along Ifon -Benin highway in southwestern Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of past road failures showed some major causes of pavement failure, varying from usage, poor design and construction problems, use of substandard material for road construction, bedrock depressions, and presence of undetected linear features, such as fractures and rock boundaries ((Momoh et al 2008;Daramola et al 2018); heavy tra c, poor maintenance culture; poor highway facilities such as drainages; poor workmanship and supervision; and non-compliance to local standard of practice. Also some failures have been attributed to inadequate knowledge of the geotechnical characteristics and geomorphology during design and construction phases.…”
Section: Introductionmentioning
confidence: 99%